Human Resource Management - Torrington, Derek; Hall, Laura; Taylor, Stephen; Atkinson, Carol (Pearson International Content, 2020)
“It is well written and students find a clarity that is missing from some other texts. It is balanced and avoids the mistake of accepting wholesale underlying assumptions about the employment relationship that some HRM books do” Dr Alan Roe, Leeds University Business School   Praised for its comprehensive scope of topics, coverage of important HRM issues and succinctness, Human Resource Management helps those aspiring to or working in HR or management roles.   This eleventh edition has been thoroughly updated with the economic, social and legal employment practice changes and is specifically designed to cover the issues and debates facing HRM today, backed up by academic research.   Main updates are: ·   New content on productivity and its impact on workplaces in Britain in a post-Brexit environment, including new material on job quality and productivity ·   The causes and implications of "presenteeism" and "Leaveism" ·   Content on the UK's ever-changing qualifications/training (much changed from last edition ·   New chapter on HR in small to medium sized enterprises (SMEs) ·   New chapter on the future of work ·   Gig economy, Brexit and Artificial Intelligence (AI) Key pedagogic features include:   ·    ‘Theory into Practice’ and ‘Putting it into Practice’ at the end of chapters enable readers to review, link and apply their understanding of the chapter to a practical business scenario ·    ‘Window on Practice’ provides illustrative material throughout the text, including examples of real company practice, survey results, anecdotes and quotations, and court cases ·    Discussion boxes are two or three short questions intended for general discussion in a tutorial or study group to encourage critical thinking and understanding ·    Activities and exercises throughout to encourage students to engage with their learning ·    Employability skills chapters cover basic skills to learn by practise.   Additional resources such as multiple choice tests and a glossary are available for students at go.pearson.com/uk/he/resources.   Human Resource Management is a great introduction to human resources for students studying on undergraduate business and management courses, as well as those on CIPD accredited courses.     About the authors Written by a close-knit team, who share each other's writing as it proceeds according to an agreed structure. All have great experience of teaching and examining HR at undergraduate, post graduate and professional level; thorough and deep research portfolios and CIPD membership Derek Torrington  is  Emeritus Professor of Management at the University of Manchester, Chartered Companion CIPD and previous Chief Examiner  Laura Hall is now a freelance academic and has carried out work for a wide range of bodies, including the CIPD. Stephen Taylor is a senior lecturer in HRM at the University of Exeter Business School, and a Chief Examiner for the CIPD. Carol Atkinson is Professor of HRM, and Associate Dean for Research at Manchester Metropolitan University Business School, and a member of the CIPD Manchester Branch Committee.